The relationship between emotional intelligence, frontline employee adaptability, job satisfaction and job performance. (May 2016) - Sony, Michael; Mekoth, Nandakumar
Abstract: Adaptable FLE's are an asset for the organization and customer alike as they are an indispensable part of service experience. They are subjected to pressures which are not found on any other positions in the organizations and displaying organizationally desired emotions play an important part in a service encounter. Therefore, the present research examines the relationship between emotional intelligence, frontline employee adaptability and job outcomes (Job Satisfaction and Job Performance). 517 FLE's working in Power utility in India participated through a cross sectional study. The research found a positive relationship between emotional intelligence and frontline employee adaptability. Specifically, all the dimensions of emotional intelligence positively impacted FLE adaptability. In addition, FLE adaptability is found to positively impact Job outcomes. The results and implications are discussed. Graphical abstract: Highlights: We examine the effects of Emotional intelligence on frontline employee adaptability. The impact of FLE adaptability on Job Satisfaction and Job Performance is studied. FLE adaptability is modeled as multidimensional second order CFA. Emotional intelligence is found to influence FLE adaptability. Work Experience moderates relationship between EI and FLE adaptability.